Integrating Economic, Environmental, and Social Dimensions: A Green Accounting Framework for Local Food-Based MSMEs - Hidayat, Muhammad Fery; Supriyadi, Supriyadi; Wellem, Karmila Alamsyah (International Ecsis Association, 2025)
This study aims to develop and validate a Green Accounting Model designed to strengthen the capacity of local food-based micro, small, and medium enterprises (MSMEs) in South Konawe Regency to support sustainable economic development and regional food security. The model was created through a combination of Research and Development (R&D) and Participatory Action Research (PAR), ensuring both methodological rigor and active engagement of MSME actors throughout the research process. Data were collected using surveys, interviews, focus group discussions (FGDs), participatory observation, and model trials with five selected MSMEs representing diverse food sectors. Initial findings reveal that MSMEs predominantly relied on simple cash inflow–outflow records and lacked systematic documentation of environmental costs, resource use, and social contributions. The proposed Green Accounting Model integrates economic, environmental, and social components into a modular and user-friendly structure. After expert validation and revision, the model was tested in the field over one month. The results show a substantial improvement in MSME recordkeeping capacity, indicating an effectiveness level of 78.2%. Qualitative insights further demonstrate enhanced sustainability awareness, routine documentation practices, and increased attention to resource efficiency. User perception scores averaged 86.2%, reflecting strong acceptance and the potential for long-term adoption. The findings confirm that a contextually adapted, simple, and integrative accounting tool can effectively bridge the gap between sustainability principles and daily MSME operations. Research implications include opportunities for broader model adoption across MSME sectors, integration into local sustainability policies, and further digitalization to enhance accessibility and impact.